2015
DOI: 10.1134/s0006297915120081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SkQ1 on expression of Nrf2 gene, ARE-controlled genes of antioxidant enzymes and their activity in rat blood leukocytes under oxidative stress

Abstract: The study demonstrated that oxidative stress induced by hyperoxia (0.5 MPa for 90 min) resulted in reduction of mRNA levels of transcription factor Nrf2 and Nrf2-induced genes encoding antioxidant enzymes (SOD1, CAT, GPx4) in peripheral blood leukocytes of rats. The changes in gene expression profiles under hyperoxia were accompanied by disbalance of activity of antioxidant enzymes in the leukocytes, namely activation of superoxide dismutase and inhibition of catalase, glutathione peroxidase, and glutathione-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Nrf2 expression in leukocytes has been described in a few in vitro studies ( 21 , 22 ). In this study, to identify the potential role of Nrf2 in the HS-induced inflammatory response, the expression pattern of Nrf2 in leukocytes was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Nrf2 expression in leukocytes has been described in a few in vitro studies ( 21 , 22 ). In this study, to identify the potential role of Nrf2 in the HS-induced inflammatory response, the expression pattern of Nrf2 in leukocytes was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Our data are generally consistent with previously published indirect data on the possible activation of the Keap1-Nrf2 signaling pathway by SkQ1. In particular, it was reported that the expression of genes of the antioxidant system (Sod1-2, Cat and Gpx4) increased after pre-treatment with SkQ1 under hypoxic conditions [22].…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of SkQ1 during oxidative stress can probably be realized not only through direct antioxidant activity but also as a result of activation of the Keap1/Nrf2/ARE signaling pathway [22]. In order to investigate the possible activation of the NRF2 transcription factor by SkQ1, we examined the level of NRF2 and NQO1 (NAD(P)H quinone dehydrogenase-1), an NRF2 target gene, in the liver of uninfected and infected animals (Figure 6).…”
Section: Nrf2 and Nqo1mentioning
confidence: 99%
“…Furthermore, GST was previously shown to be activated by Nrf2 in response to oxidative stresses caused by xenobiotics (Chen et al 2018). Moreover, Nrf2 has been previously shown to elevate the transcriptional activity of the target genes encoding antioxidant enzymes like GPX4 (Vnukov et al 2015). Phosphorylated H2AX induced by ATM (called γH2AX) has been implicated in the damage repair processes responding to DNA double-strand breaks, indicating the potential of γH2AX as a promising molecular marker of DNA damage (Siddiqui et al 2015).…”
Section: Discussionmentioning
confidence: 99%